GODIANISM: FROM A LOCAL BLACK PROTEST TO A QUEST FOR WORLD PEACE - Onunwa, Udobata (Journal of Dharma, 1989)
The study of the New Religious Movements in Africa is fraught with a lot of problems. It is involving and exerting in its demands of intellectual resources, time, patience and objectivity. More often than not, there is such a careful reconstruction of the history and development of a group that its factual history is lost. Some researchers therefore fall back to the only available data which had been properly reconstructed and distorted by some enlightened members of the group. Such careful reconstructions are out to project a particular point of view. A case in point is Godianism in Africa. This is a movement that is currently gaining grounds in many parts of Africa and among many Afro-Americans but its history has not been accurately presented in its right context. From the current write-ups and oral presentation of facts, one is made to believe and accept that Godianism which claims to be the "traditional religion for modern man" was originally begun as an indigenous religious revivalist movement. Consequently the hard time the Blacks passed through, their ingenuity and perseverance in the face of obstacles are glossed over.